Pengaruh Kompetensi Guru Akidah Akhlak Dan Authoritative Parenting Style Terhadap Karakter Holistik Siswa Dengan Kinerja Guru BK Sebagai Variabel Moderasi - Arina Diana; Ahmad Thoyyib Mas'udi; Qomaruddin Qomaruddin (Pascasarjana Universitas Qomaruddin, 2024)
In Indonesia, character education must take center stage in all spheres of education, including formal, non-formal, and informal learning. The ability of the instructor's aqidah morality, parenting style, and counseling teacher performance are only a few of the variables that influence how children grow their character. With the performance of counseling teachers as a moderating variable in MA Ihyaul Ulum Cangaan Ujungpangkah Gresik, this study aims to determine the effect of parenting style, particularly the type of authoritative parenting style, and the competence of PAI teachers on the holistic character of students. This study employs an affiliation or associative method and is quantitative in nature. All MA Ihyaul Ulum students from three classes totaling 75 people made up the population of this study. By calculating the number of samples using the Michael and Issac method with a 5% error rate, the sample in this study was chosen using a straightforward random sampling technique. This study was carried out in Gresik at MA Ihyaul Ulum Cangaan. This study's instrument was a closed questionnaire that was completed online using a Google form. The Likert scale was used to create the questionnaire (questionnaire). Technical data analysis employing the moderation regression test, t test, and F test.